Early Outcome of Endoscopic Trans-nasal Trans-sphenoidal Pituitary Surgery in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Endoscopic trans-nasal trans-sphenoidal hypophysectomy is a minimally invasive surgical procedure aimed at resection of pituitary tumors. This technique is widely practiced in developed countries but is presently gaining popularity in our environment. This study was aimed at presenting our preliminary outcomes as it relates to the technique of endoscopic trans-nasal trans-sphenoidal pituitary surgery in Kano, Nigeria. This was a retrospective study of patients with pituitary tumors that presented at a government tertiary and private specialist health institutions from October 2018 to December 2019. They all had excision of varying degrees of pituitary tumors via endoscopic trans-nasal trans-sphenoidal approach under general anesthesia. There were 4 females (66.7%) and 2 males (33.3%) and their ages ranged between 25 – 60 years. They presented with varying degrees of clinical symptoms such as gynaecomastia, galactorrhea, irregular menstruation, infertility, intermittent headache and visual impairment. Four (66.7%) had complete tumor excision and 2 (33.3%) had incomplete excision. Four (66.7%) had complete symptom relief and 2 (33.3%) had significant improvement in symptoms. The complications of surgery were nasal septal adhesion 1(16.7%), CSF leak 1(16.7%) and transient diabetes insipidus 2(33.3%). All complications were resolved during admission and at follow up visits. Histopathological analysis of specimens confirmed 5 cases of pituitary adenoma and a case of pituitary Rathkes cleft cyst. Endoscopic trans-nasal trans-sphenoidal pituitary surgery is feasible and has a favorable outcome in our setting with prospects for improvement to ensure safety. Keywords: Nasal endoscopy, Sinus surgery, Pituitary tumors, Skull base, Hypophysectomy.